Acculturation and Health: The Moderating Role of Sociocultural Context. Issue 3 (September 2017) - Fox, Molly; Thayer, Zaneta M.; Wadhwa, Pathik D.
ABSTRACT: Acculturation represents an important construct for elucidating the determinants and consequences of health disparities in minority populations. However, the processes and mechanisms underlying acculturation's effects on health are largely undetermined and warrant further study. We integrate concepts from anthropology and statistics to describe the role of sociocultural context as a putative modifier of the relationship between acculturation and health. Sociocultural context may influence the extent to which exposure to host culture leads to internalization of host cultural orientation and may influence the extent to which acculturation leads to stress and adoption of unhealthy behaviors. We focus on specific aspects of sociocultural context: (1) neighborhood ethno‐cultural composition; (2) discrimination; (3) discrepancy between origin and host environments; (4) discrepancy between heritage and host cultures; (5) origin group, host group, and individual attitudes toward assimilation; (6) variation in targets of assimilation within host community; (7) public policy and resources; and (8) migration selection bias. We review and synthesize evidence for these moderation effects among first‐ and later‐generation immigrants, refugees, and indigenous populations. Furthermore, we propose best‐practices data‐collection and statistical‐analysis methods for this purpose, in order to improve our understanding of the complex, multilevel aspects of the relationship between acculturation and health. [ acculturation, minority health, health disparities, sociocultural context, effect moderation, statistical interaction ]